(untitled) (Economic and Political Thought, 2018)
For a very long time, the creation of the best conditions in the situation when a professional career ends has been a problem for society. The elderly’s inability to maintain themselves has led to efforts to improve their living conditions. The ways of dealing with this problem were varied and changed along with economic, social and political changes. Responsibility in this area lies with the insurance sector. Recent reports have highlighted the fact that the low level of births is accompanied by a low level of mortality. The aging of the population is a process generally known in society. Hardly anyone, however, realizes that it is the fastest in Europe. Every two years, the European Commission publishes the European Demographic Report indicating the latest facts and demographic trends in the member countries. The growing share of older people in the structure of society is the main effect of this change. The pension system is very sensitive to any changes. The existing factors make it necessary to introduce new solutions so that it can function properly. The functioning of pension systems is perceived by society as a social sphere. At the same time, the amount of pension benefits depends on economic development and the changing economic situation in Poland. There were Open Pension Funds established to invest the funds from contributions in order to multiply them. However, their activity was based on market risk and did not guarantee citizens the benefits of participation (according to some experts). According to the authors of the article, another change, i.e. limiting the investment in OPF, will not improve the whole situation. It is only saving ZUS to enable it to pay current and future pensions needed in a short-term period. Of course, there will be many such discussions, but will the pensioners’ situation get better? Obviously, the topic is still a matter for social debate.